STUDENTS' PERCEPTION AND MOTIVATION TOWARD ENGLISH THROUGH GOOGLE MEET TO THE ELEVENTH GRADE STUDENTS ATSMA PRESTASI PRIMA ACADEMIC YEAR 2020/2021 - Hestia Ayu Pramaisella; Saptanto Hari Wibawa; Agung Budi Kurniawan (The Journal Of English Teaching For Young And Adult Learners, 2022)
Along with the development of science, learning English is very important for students to master orlearn. However, with the COVID-19 outbreak, learning activities are carried out at home using theGoogle Meet media. This study aims to determine students' perceptions and motivations towardsEnglish through google meet in class XI students of SMA Prestasi Prima for the academic year2020/2021. This type of research is descriptive qualitative data taken from 30 students of class XIIPA 1. Data collection techniques using observation, questionnaires, and interviews. Then theresearch instrument used field notes, questionnaire sheets, and cellphones, and the Whatsappapplication. Then analyze the data using data reduction data, display the data, and conclude. Theresults of this study are presented descriptively. Then this study found that the perception ofstudentslearning English through Google Meet was quite good. However, students experience obstacles inonline learning, such as difficulties understanding the material, network disturbances, and internetdata packages that run out quickly. While students' motivation to take part in online learning is quitegood, this can be seen from the way studentsthink they are still diligent in doing assignments andrepeating material that has not been understood. However, some students are not enthusiastic aboutlearning English through google meet. This can be seen from the attitude of students who are lazy tostudy because theyhave a lot of assignments and feel bored with the assignments given repeatedly